HISTOPATHOLOGICAL STUDY OF NON-NEOPLASTIC LESIONS OF SKIN - ITALIYA, SWETA; PUROHIT, ASHA; GOHEL, ARPIT; Prajapati, Hitesh (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were as follows: (1) To find the prevalence of various non-neoplastic skin lesions in our tertiary care hospital. (2) To study the age- and sex-wise distribution of non-neoplastic skin lesions. (3) To compare the results of the present study with other studies. Methods: The present study comprised total 200 punch biopsy specimens of diagnosed cases of non-neoplastic lesions of skin, detailed clinical data, age, sex, and sites of skin lesion of patients which were included in the study. Specimens received were fixed in 10% formalin. Biopsy bits were submitted as whole and processed in automated tissue processor for routine paraffin embedding. Results: A total of 200 lesions were analyzed. Maximum cases were in the age group of 21–30 years followed by 31–40 years age. Fifty-five (27.5%) cases were of non-infectious erythematous, papular, and squamous diseases followed by 54 (27%) cases of vesiculobullous and vesiculopustular diseases, 37 (18.5%) cases of bacterial diseases, 20 (10%) cases of fungal diseases, and 34 (17%) cases of vascular lesions, connective tissue disorders, non-infectious granulomas, perforating disorders, etc. Conclusion: Skin lesions were common in males than in females with male: female ratio of 1.38:1. Younger age group was more commonly affected. Non-infectious erythematous, papular, and squamous lesions were most common with psoriasis being the most common followed by non-infectious vesiculobullous and vesiculopustular lesions with pemphigus vulgaris being the most common, followed by infective lesions consisting of bacterial, fungal, and viral lesions. Other lesions consisted of vascular skin lesions, connective tissue disorders non-infectious granulomas, perforating disorders, etc.